High deformation multifunctional composites: materials, processes, and applications - Costa, Pedro, (2020)
Structural health monitoring (SHM) is a non-destructive process of collecting and analysing data from structures to evaluate their conditions and predict the remaining lifetime. Multifunctional sensors are increasingly used in smart structures to self-sense and monitor the damages through the measurements of electrical resistivity of composites materials. Polymer-based sensors possess exceptional properties for SHM applications, such as low cost and simple processing, durability, flexibility and excellent piezoresistive sensitivity. Thermoplastic, thermoplastic elastomers and elastomer matrices can be combined with conductive nanofillers to develop piezoresistive sensors. Polymer, reinforcement fillers, processing and design have critical influences in the overall properties of the composite sensors. Together with the properties of the functional composites, environmental concerns are being increasingly relevant for applications, involving advances in materials selection and manufacturing technologies, In this scenario, additive manufacturing is playing an increasing role in modern technological solutions. Stretchable multifunctional composites applications include piezoresistive, dielectric elastomers (mainly for actuators), thermoelectric, or magnetorheological materials [1]. In the following, piezoresistive materials and applications will be mainly addressed based on their increasing implementation into applications.